Characteristics associated with anti-osteoporosis medication use: data from the Global Longitudinal Study of Osteoporosis in Women (GLOW) USA cohort - Guggina, Pamela (Bone, 2012)
INTRODUCTION: Many women at risk of fracture do not receive anti-osteoporosis medication (AOM), while others may be receiving unnecessary treatment. PURPOSE: To examine the characteristics associated with AOM use among women at low and high risk of fracture. METHODS: The Global Longitudinal Study of Osteoporosis in Women (GLOW) is a prospective cohort study in which data were collected, via self-administered questionnaires, from 60,393 non-institutionalized women aged ≥55 years in 10 countries between October 1, 2006 and April 30, 2008. This is a cross-sectional analysis of baseline USA data, in which women were classified as having low fracture risk (<65 years; no FRAX risk factors) or high fracture risk (≥65 years; prior fracture or ≥2 other FRAX risk factors). RESULTS: Of 27,957 women, 3013 were at low risk of fracture and 3699 were at high risk. Only 35.7% of high-risk women reported AOM treatment, rising to 39.5% for those with self-reported osteopenia and 65.4% for those with self-reported osteoporosis. Conversely, 13.4% of low-risk women reported AOM, rising to 28.7% for osteopenia and 62.4% for osteoporosis. Characteristics associated with significantly higher AOM treatment rates among low-and high-risk women were: osteoporosis (odds ratios 75.3 and 18.1, respectively), osteopenia (17.9 and 6.3), concern about osteoporosis (2.0 and 1.8), higher perceived risk of fracture (2.3 and 1.6), and higher vitality score (1.7 and 1.6). CONCLUSION: Use of AOM is frequently inconsistent with published guidelines in both high -and low-risk women. Characteristics other than FRAX fracture risk appear to influence this use, particularly the presence of self-reported osteoporosis.